Heuristic Search: The Emerging Science of Problem Solving - Salhi, Saïd (SpringerLink, 2017)
This book aims to provide a general overview of heuristic search, to present the basic steps of the most popular heuristics, and to stress their hidden difficulties as well as their opportunities. It provides a comprehensive understanding of Heuristic search, the applications of which are now widely used in a variety of industries including engineering, finance, sport, management and medicine. It intends to aid researchers and practitioners in solving complex combinatorial and global optimisation problems, and spark interest in this exciting decision science-based subject. It will provide the reader with challenging and lively methodologies through which they will be able to design and analyse their own techniques